Association of Troponin, C-Reactive protein, Albumin and C-Reactive protein/Albumin Ratios with Mortality in Intensive Care Unit Patients with Community-acquired Pneumonia - Halil İbrahim Doru; Furkan Akpınar; Şenol Arslan; Nazım Onur Can (Acta Medica Alanya)
Aim: Parameters used to determine prognosis in community-acquired pneumonia (CAP) patients often have limited clinical value. This study aims to examine the efficacy of CRP, albumin, CRP/albumin ratio and troponin elevation in predicting 30-day mortality in patients hospitalized in the intensive care unit with CAP.Material and Methods: In this study, 200 patients (85 females and 115 males) older than 18 years of age with a diagnosis of CAP who were followed up in the intensive care unit after emergency department admission between January 1, 2023 and January 1, 2024 were included. Patients who underwent chest radiography and biochemical analyses, including complete blood count, CRP and albumin, within the first 24 hours, were divided into two groups: those who died and those who survived. Troponin, CRP, albumin, and CRP/albumin ratios were compared between the groups about mortality.Results: The findings obtained in our study were as follows: Troponin, CRP, albumin and CRP/albumin ratio values differed significantly in patients with mortality. When ROC analysis was performed to determine the power of troponin, CRP, albumin and CRP/albumin ratio to predict mortality in the emergency department, it was found that troponin value was the strongest marker in terms of sensitivity with 82.25%. In terms of specificity, low albumin was the most specific parameter, with 82.50% and CRP/albumin ratio followed albumin with 72.50%. Conclusion: We believe that CRP, albumin, CRP/albumin and troponin are significant predictors of 30 day mortality in patients with CAP hospitalized in the intensive care unit.